How can patients with Clostridioides difficile infection on concomitant antibiotic treatment be best managed?. Issue 11 (November 2022) - Fitzpatrick, Fidelma; Safdar, Nasia; van Prehn, Joffrey; Tschudin-Sutter, Sarah
Summary: Antibiotics are modifiable risk factors for Clostridioides difficile infection (CDI), driving pathogenesis via gut microbiome disruption. The management of patients with CDI prescribed concomitant non-CDI antibiotics is problematic and influences CDI outcome and recurrence risk. Though an assessment of the ongoing requirement for concomitant antibiotics is essential, discontinuation is often not possible. Antibiotics for other reasons might also need to be commenced during CDI therapy. Attempts to minimise the number and duration of antibiotics with a change to a low-risk class are recommended. Fidaxomicin might be preferable to vancomycin due to it having less effect on the gut microbiome; however, vancomycin is also acceptable. Metronidazole should be avoided and proton pump inhibitors discontinued. Access to fidaxomicin might be limited; hence, it should be prioritised for patients at high risk of recurrence. There is insufficient evidence to support extending anti-CDI therapy duration and concerns regarding microbiome effect remain. The addition of bezlotoxumab might be considered if multiple additional risk factors for recurrent CDI exist, though the amount of evidence is low. Investigational approaches to reduce the effect of concomitant antibiotics on the gut microbiome could further optimise CDI treatment in the presence of concomitant antibiotic use in the future.